Trends in seizures of powders and pills containing illicit fentanyl in the United States, 2018 through 2021 - Palamar, Joseph J.; Ciccarone, Daniel; Rutherford, Caroline; Keyes, Katherine M.; Carr, Thomas H.; Cottler, Linda B. (Drug and alcohol dependence, 2022)
Prevalence of fentanyl-laced counterfeit prescription pills has been increasing in the US, possibly placing a wider population at risk for unintentional exposure. We aimed to determine whether there have been shifts in the number of fentanyl seizures and in the form of fentanyl seized in the US. We examined quarterly national seizure data from High Intensity Drug Trafficking Areas to determine the number of drug seizures in the US containing fentanyl from January 2018 through December 2021. Generalized additive models were used to estimate trends in the number and weight of pill and powder seizures containing fentanyl. There was an increase both in the number of fentanyl-containing powder seizures (from 424 in 2018 Quarter 1 [Q1] to 1539 in 2021 Quarter 4 [Q4], β = 0.94, p < 0.001) and in the number of pill seizures (from 68 to 635, β = 0.96, p < 0.01). The proportion of pills to total seizures more than doubled from 13.8% in 2018 Q1 to 29.2% in 2021 Q4 (β = 0.92, p < 0.001). Weight of powder fentanyl seizures increased from 298.2 kg in 2018 Q1 to 2416.0 kg in 2021 Q4 (β = 1.12, p = 0.01); the number of pills seized increased from 42,202 in 2018 Q1 to 2,089,186 in 2021 Q4 (β = 0.90, p < 0.001). Seizures of drugs containing fentanyl have been increasing in the US. Given that over a quarter of fentanyl seizures are now in pill form, people who obtain counterfeit pills such as those disguised as oxycodone or alprazolam are at risk for unintentional exposure to fentanyl. •We examined trends in fentanyl seizures in the US from 2018 through 2021.•The number of seizures of pills and powders containing fentanyl increased.•The volume and number of fentanyl-containing pills also increased.•The percentage of seizures in pill form increased from 13.8% in 2018 to 29.2% in 2021.•Fentanyl in pill form is increasingly prevalent and unintentional exposure is of concern.